Intravenous versus Intra-articular Tranexamic Acid in Patients Undergoing Primary Unilateral Total Knee Arthroplasty: A Prospective Randomized Double Blinded Non-inferiority Trial. Issue 2 (16th February 2016) - Macdessi, Samuel; Chen, Darren; Goyal, Navendu; Harris, Ian; Kirsh, George; Rowden, Neville
Objectives: Tranexamic acid (TXA) is commonly used in primary total knee arthroplasty (TKA) to reduce blood loss, however the most appropriate route of administration is still debated. This study was conducted to compare the two most commonly used routes of TXA administration, intravenous (IV) and intra-articular (IA). Methods: This study was conducted as a non-inferiority, double blinded randomized trial to compare IA TXA with IV TXA in terms of efficacy in reducing blood loss as measured by post-operative Hb drop and transfusion rates. We hypothesized that IA TXA is not inferior to IV TXA in reducing blood loss and transfusion requirements. Results: One hundred and sixty eight patients were analysed. Mean day 1 and day 2 post-operative Hb values for both the groups were statistically similar (p=0.88, p=0.95 respectively). Also, no statistical difference was seen on comparison of change in Hb between pre-operative and day 1 or day 2 values (p=0.55, p=0.58 respectively). There were no transfusions given in either group. Conclusion: Intra-articular TXA is non-inferior to IV TXA in terms of fall in Hb and blood transfusion requirements. This trial further establishes and supports the use of IA TXA for primary TKA.